Increasing Vocabulary Mastery of the First Year Students of MTs Yasis At Taqwa Through Concept Mapping Strategy - Zaenul Wafa (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
Increasing Vocabulary Mastery of The First Year Students of MTs Yasis At Taqwa Through Concept Mapping Strategy. This study is to see increasing vocabulary mastery of the first year students of MTs Yasis At Taqwa through concept mapping strategy..The subject of this research is VII B class which is consisted of 20 students. The sample was taken by using random sampling. The design in this research was pre-experimental with pre-test and post-test design. The students did the pre-test, got the treatment and did the post-test. It aimed to know whether concept mapping strategy can increase the students’ vocabulary mastery. The result in this research was indicated that there was improvement of the students’ vocabulary mastery. it was indicated by the students’ mean score of post-test (1,88) was greater than pre-test (3,27). Even, for the level significant (p) 5% and df = 19, and the value of table is 1,729, while the value of t-test is 27,22. it means that, the t-test value is greater than t-table (27,22 ≥ 1,729). Thus, it can be concluded that the students vocabulary mastery is significant better after getting the treatment. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.